Penilaian Kesehatan Bank Perkreditan Rakyat Syariah (BPRS) ABC - Arfan Anugrah Asyhari; Rangga Putra Ananto; Eka Rosalina (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2021)
This study aims to determine the Bank Soundness Level with the object of Islamic Rural Banks registered with the Financial Services Authority in 2015-2019. The type of the research that used in this research is descriptive research with a qualitative approach. Assessment using the Risk-Based Bank Rating (RBBR) method consists of four factors, namely the Risk Profile, Good Corporate Governance, Earnings and Capital of each bank. The Risk Profile consists of credit risk and liquidity risk. Credit risk is measured using NPF and liquidity risk is measured using FDR. Earnings factor is measured by ROA and NIM ratio, Capital factor is calculated by CAR ratio. The results showed that the results obtained the predicate of being unhealthy and even quite healthy on the NPF, FDR, ROA, and NIM ratios, while the CAR ratios for the last 3 years received the predicate Very Healthy appropriate to Bank Indonesia regulations, which exceeded 12% ABSTRAK Penelitian ini bertujuan untuk mengetahui Tingkat Kesehatan Bank dengan objek Bank Perkreditan Rakyat Syariah yang terdaftar di Otoritas Jasa Keuangan pada tahun 2015-2019. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian desktiptif dengan pendekatan kualitatif. Penilaian dengan metode Risk-Based Bank Rating (RBBR) terdiri dari empat faktor yaitu Risk Profile, Good Corporate Governance, Earnings dan Capital dari setiap bank. Risk Profile terdiri dari risiko kredit dan risiko likuiditas. Risiko kredit diukur dengan menggunakan NPF dan risiko likuiditas diukur dengan menggunakan FDR. Faktor Earnings diukur dengan rasio ROA, ROE dan NIM, faktor Capital dihitung dengan rasio CAR. Hasil penelitian menunjukkan hasil yang memperoleh predikat kurang sehat bahkan cukup sehat atas rasio NPF, FDR, ROA, ROE dan NIM, sedangkan pada rasio CAR pada 3 tahun terakhir memperoleh predikat Sangat Sehat sesuai ketentuan Bank Indonesia yaitu melebihi 12%.